2007
DOI: 10.1111/j.1524-6175.2007.07194.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Antihypertensive Drug Class on Patient Persistence and Compliance in a Usual‐Care Setting in the United States

Abstract: T he prevalence of hypertension has continued to rise over the past decades, reaching 31.3% for 1999-2000, 1 possibly as the result of better detection and more specific definitions. only 37% of all patients with hypertension and only 57% of those receiving antihypertensive medication in the united states currently have controlled blood pressure (bp). 2 This is an improvement over prior years, as the national Health and nutrition Examination survey (nHanEs) iii indicated that during the time period of 1991 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
5
22
0
1
Order By: Relevance
“…Clinically appropriate reasons to avoid use of thiazides exist, including electrolyte abnormalities, orthostatic hypotension, and patient preference or nonadherence. 21,22 In fact, the higher likelihood of adverse effects and contraindications (e.g. orthostatic hypertension) seen with older age plausibly explains the age association with lower thiazide use reported here.…”
Section: Discussionmentioning
confidence: 66%
“…Clinically appropriate reasons to avoid use of thiazides exist, including electrolyte abnormalities, orthostatic hypotension, and patient preference or nonadherence. 21,22 In fact, the higher likelihood of adverse effects and contraindications (e.g. orthostatic hypertension) seen with older age plausibly explains the age association with lower thiazide use reported here.…”
Section: Discussionmentioning
confidence: 66%
“…ARBs have the highest rate of treatment persistence and compliance among anti-hypertensives [23][24][25][26] . For a successful management of hypertension, and other chronic conditions, compliance and persistence are important.…”
Section: Introductionmentioning
confidence: 99%
“…After 1 year, the proportion of patients still taking the initially prescribed medication was 52% for angiotensin II receptor blockers, 48% for angiotensin-converting enzyme inhibitors, 40% for beta-blockers, 38% for calcium antagonists, and 30% for diuretics. 18 Compared with patients receiving diuretics, those treated with other antihypertensive agents were significantly less likely to discontinue therapy. 18 A recent metaanalysis confirms highest adherence to angiotensin II receptor blockers and angiotensin-converting enzyme inhibitors, and lowest adherence to diuretics and beta-blockers.…”
Section: Factors Related To Medicationtaking Behavior In Hypertensionmentioning
confidence: 99%
“…18 Compared with patients receiving diuretics, those treated with other antihypertensive agents were significantly less likely to discontinue therapy. 18 A recent metaanalysis confirms highest adherence to angiotensin II receptor blockers and angiotensin-converting enzyme inhibitors, and lowest adherence to diuretics and beta-blockers. 19 In a study of 588 hypertensive patients, intentional nonadherence was reported by 9% of the participants, compared with 31% who reported unintentional nonadherence.…”
Section: Factors Related To Medicationtaking Behavior In Hypertensionmentioning
confidence: 99%